An intelligence technique to maximize power generation using solar panel and its maintenance - Veena KN, Nikhita Jalapure, Nayankumar.M, Naveen Sai Chandra K, Harshvardhan T (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Earth receives the maximum amount (174 Peta Watts) of radiation from the upper atmosphere. Approximately 30% is reflected to space while the remainder is absorbed. Solar energy is an alternate for fossil fuels because it is non-polluting, clean, reliable, and renewable source of energy. It does not pollute the air by releasing harmful gases to the environment like carbon dioxide, nitrogen oxide or Sulphur oxide. So, the risk of damage is reduced. Thus, the utilization of solar devices was more suggested and therefore the traffic light and streetlights in villages was installed using solar array, but the solar PV modules are generally employed within the dusty environments and therefore the dust gets accumulated on the front surface of the module and blocks the incident light form the sun and it reduces the facility generation capacity of the module, the power output reduces if the module is not cleaned for a frequently. In order to regularly clean the dust, this research presents a control application of a sun tracker that can follow the sun with high accuracy and clean the dust on the panel without requiring a precise process of installation or recalculation. The designed tracking system include sensors, microcontroller, drivers for dc motors and gear- bearing arrangements with supports and mountings. DC motor is used to move the system panel in order that sun’s beam is in a position to stay aligned with the solar array and also clean the dust on the panel by wiping the panel using wipers which improves the efficiency of the solar array. Simulation and experimental results are obtained from a low-cost single axis solar tracker and exposed. Energy saving factors are taken under consideration, which means that, among other factors, the sun is not constantly tracked with an equivalent accuracy, to stop energy over consumption by the motors.